Possibilities of using plasma techniques of surface engineering for modification of polymer membranes - Kacprzyńska-Gołacka, J.; Kowalik-Klimczak, A.; Skowroński, J.; Rajewska, P.; Wieciński, P.; Smolik, J. (Polimery, 2021)
The paper discusses the possibilities of using low temperature plasma in activating the surface layer of polymer membranes and depositing ultra-thin metallic layers on their surface. It has been found that the above surface engineering techniques enable effective modification of functional properties of polymer membranes, which are important in high-efficiency water and wastewater treatment.